New sedimentary unit with subaqueous facies of Curitiba Sedimentary Basin, Southern Brazil - Angulo, Rodolfo Jose; Souza, Maria Cristina de; Scardia, Giancarlo [UNESP]; Salamuni, Eduardo; Arai, Mitsuru [UNESP]; Parenti, Fabio; Veiga, Luis Augusto Koenig (Soc Brasileira Geologia, 2024)
The Curitiba Sedimentary Basin (CSB) is a small and shallow sedimentary basin, which is part of the Continental Rift of Southeastern Brazil. New exposures allowed for the identification of a subaqueous facies association, named Guatupe Unit, within the Guabirotuba Formation. For the first time in the CSB, sedimentary facies clearly deposited within a subaqueous environment, probably a swamp, are described and consists of wavy heterolithic and massive mud with linsen. In addition, mudflow deposits entering the water body are also identified and documented by massive sand facies with organic matter and load structures at their base. The latter indicates that the underlying sediments were plastic and contemporary. These sedimentary features, associated with palynoflora and a fossil trunk tree, indicate that the climate was humid enough to maintain permanent water bodies, like swamps, and vegetation, including trees. Other facies of the Guatupe Unit document mudflows and channelized tractive fluxes, whose association indicates that they were probably deposited in an alluvial fan environment. The facies, facies association, depositional processes, environment, and Miocene age of the Guatupe deposit are quite different from the previous sedimentary units reported for CSB sedimentary infill and the original definition of the formations.
Keywords: Guatupe; Guabirotuba Formation; Curitiba Basin; Cenozoic; South America